2003
DOI: 10.1086/375156
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Confirmation of a Substantial Population of Luminous Red Galaxies at Redshifts z 2

Abstract: We confirm spectroscopically the existence of a population of galaxies at z ∼ > 2 with rest-frame optical colors similar to normal nearby galaxies. The galaxies were identified by their red near-infrared colors in deep images obtained with ISAAC on the Very Large Telescope of the field around the foreground cluster MS 1054-03. Redshifts of six galaxies with J s − K s > 2.3 were measured from optical spectra obtained with the W. M. Keck Telescope. Five out of six are in the range 2.43 ≤ z ≤ 3.52, demonstrating … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
114
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(127 citation statements)
references
References 26 publications
13
114
0
Order By: Relevance
“…In the next model, we introduce number-density evolution of the elliptical population parameterized using φ ∝ (1 + z) −2 . The formation redshifts is set to z f = 4.0 for all galaxy types, being in more agreement with the evolved red galaxies found at z > 2 (van Dokkum et al 2003;Daddi et al 2004). The evolution in the early-type densities was not accompanied by an evolution in M , arguing that a substantial number of ellipticals formed in spiral-spiral mergers as expected for hierarchical galaxy formation.…”
Section: Comparison With Models Of Evolutionsupporting
confidence: 59%
“…In the next model, we introduce number-density evolution of the elliptical population parameterized using φ ∝ (1 + z) −2 . The formation redshifts is set to z f = 4.0 for all galaxy types, being in more agreement with the evolved red galaxies found at z > 2 (van Dokkum et al 2003;Daddi et al 2004). The evolution in the early-type densities was not accompanied by an evolution in M , arguing that a substantial number of ellipticals formed in spiral-spiral mergers as expected for hierarchical galaxy formation.…”
Section: Comparison With Models Of Evolutionsupporting
confidence: 59%
“…The picture becomes more controversial at higher redshifts, where the evolution of the near-IR luminosity function and cosmic stellar mass density is faster, and the properties and role of the massive galaxies found at 1.5 < z < 3 (e.g. Franx et al 2003;van Dokkum et al 2003;Daddi et al 2004a;Glazebrook et al 2004;Cimatti et al 2004;Saracco et al 2004) have still to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…5 shows the evolution of J − K colour, suggesting that an old elliptical galaxy with R − J ≥ 5 and redshift z ∼ 1.4 would have J − K ≥ 2.25. This is consistent with the results of van Dokkum et al (2003), who found galaxies with J s − K s = 2.35 and redshifts of z > 1.2 (∼17% of the sample) and z > 2.3 respectively. Finding such an elliptical galaxy at even higher redshift requires a J − K colour around 3 (for z f = 5) and higher (for z f = 10), according to our models.…”
Section: The Relevance Of the R − J ≥ 5 Colour Criterionsupporting
confidence: 93%